2015
DOI: 10.1002/hed.24200
|View full text |Cite
|
Sign up to set email alerts
|

Trends in treatment and survival for advanced laryngeal cancer: A 20‐year population‐based study in The Netherlands

Abstract: From 1991 to 2010 total laryngectomy as primary treatment modality for advanced laryngeal cancer decreased and RT increased. T3 disease showed similar survival rates for all primary treatment modalities. For T4 disease, total laryngectomy (+ adjuvant RT) showed the best survival. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1247-E1255, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 25 publications
8
58
0
4
Order By: Relevance
“…Larynx cancer is among the most frequently diagnosed head and neck squamous cell cancers (SCC), and approximately 40% of patients present with advanced disease . The 5‐year overall survival (OS) of the advanced (T3T4) tumors varies between 34% and 49%, depending on patient‐related factors, tumor‐related factors, and treatment . Historically, patients with advanced larynx cancer were treated with a total laryngectomy (TL) with adjuvant radiotherapy (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Larynx cancer is among the most frequently diagnosed head and neck squamous cell cancers (SCC), and approximately 40% of patients present with advanced disease . The 5‐year overall survival (OS) of the advanced (T3T4) tumors varies between 34% and 49%, depending on patient‐related factors, tumor‐related factors, and treatment . Historically, patients with advanced larynx cancer were treated with a total laryngectomy (TL) with adjuvant radiotherapy (RT).…”
Section: Introductionmentioning
confidence: 99%
“…A study with 5,394 patients with T3 and T4 laryngeal cancer of the SEER tumor registry revealed an increase of the percentage of non-surgically treated patients from 32% to 62% from 1992 to 2009 [134]. An evaluation of 14,000 patients with laryngeal cancer of the Dutch cancer registry confirmed this tendency [135]. The mortality after total laryngectomy amounted to 1.4% in the US in 1997 and 1.1% in 2008 [133].…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
“…Patients with T4 laryngeal cancer revealed a significant difference of the 5-year survival rate. After total laryngectomy ± adjuvant radiotherapy it amounted to 48%, after primary radiotherapy to 34%, and after primary radiochemotherapy to 42% [135]. An evaluation of 221 patients with T4 carcinomas performed by Rosenthal et al [142] revealed a significantly better local control after total laryngectomy and postoperative radiotherapy in comparison to larynx preservation protocols.…”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%
“…In the last decades, concurrent chemoradiotherapy (CRT) or radiotherapy (RT) alone have been shown to be successful in sparing the larynx in the majority of patients while reaching almost similar overall survival (OS) rates . Recent publications, however, demonstrated that in more advanced tumors TL still seems to give the best OS rates . These publications have led to an update in the American Society of Clinical Oncology guidelines in 2018, which now states that extensive (T)3 or large T4a lesions might achieve better survival rates following total laryngectomy .…”
Section: Introductionmentioning
confidence: 99%